EXPLORING THE ROLE OF DIET IN ALLEVIATING SYMPTOMS OF PREMENSTRUAL SYNDROME [PMS]: A NARRATIVE REVIEW - Febriana, Romadhinniar; Sartika, Dian; Fernandes, Alcinda Pinto; Amalia, Fany Hardiati; Putri, Frilya Rachma (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2026)
Introduction: Premenstrual Syndrome (PMS) involves physical and emotional symptoms that occur before menstruation, affecting most women of reproductive age. This study aims to review the role of nutrition and dietary interventions in alleviating PMS symptoms, with a focus on calcium, magnesium, vitamin D, and vitamin B6. Methods: Peer-reviewed articles from the past five years focused on nutrition and PMS. Data sources included PubMed, Google Scholar, and ScienceDirect. Keywords included